Inovasi dan Tata Kelola dalam Pengungkapan Emisi Karbon Manufaktur Indonesia - Yanti, Evi; Haryanto, Hery; Suprapto, Yandi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Manufacturing companies contribute significantly to carbon emissions, making transparency in carbon emission disclosure an important issue in supporting environmental sustainability. However, the level of carbon emission disclosure in Indonesia still varies and is influenced by internal company factors. This study aims to analyze the effect of green innovation on carbon emission disclosure and examine the moderating role of internal governance, which consists of ownership concentration, executive political connections, and director compensation. This study is a quantitative study with a causal approach using secondary data. The research sample included 154 manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period with a total of 770 observations. The analysis technique used is ordinary least squares (OLS) to test the relationship between variables and moderating effects. The results show that green innovation has a significant negative effect on carbon emission disclosure. In terms of moderating variables, ownership concentration and executive political connection are not proven to moderate this relationship. Meanwhile, director compensation was found to moderate the relationship between green innovation and carbon emission disclosure in a negative direction, indicating that the director compensation system actually weakens the transparency of carbon emission disclosure. The novelty of this study lies in the simultaneous testing of internal governance mechanisms as moderating variables in the relationship between green innovation and carbon emission disclosure in the context of manufacturing companies in Indonesia. This study contributes theoretically to the literature on environmental accounting and corporate governance, as well as providing practical implications for management and regulators in formulating sustainability and environmental transparency policies.